De l'esprit - Helvétius 1715-1771; Châtelet, François 1925-1985 (Paris Marabout, 1973)
In 1758 Helvétius published his philosophical magnum opus, a work called De l'esprit (On Mind), which claimed that all human faculties are attributes of mere physical sensation, and that the only real motive is self-interest, therefore there is no good and evil, only competitive pleasures. Its atheistic, utilitarian and egalitarian doctrines raised a public outcry, and the Sorbonne publicly burned it in 1759, forcing Helvétius to issue several retractions.
Claude Adrien Helvétius (1715-1771) was a French philosopher, freemason and littérateur.
Keywords: 18th Century (1701-1800); Philosophy; Crescendo; Religion; France